Respon Pertumbuhan Miselium Beberapa Isolat F3 Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA pada Media PDA dengan pH yang Berbeda - Zelita Hariani; Ani Lestari; Fawzy Muhammad Bayfurqon; Winda Rianti (JURNAL AGROPLASMA, 2023)
Mushroom seeds are an important factor to determine the success of mushroom cultivation. The growth of straw mushroom on PDA media is influenced by the degree of acidity (pH). This research was conducted at the Biotechnology and Plant Breeding Laboratory, Faculty of Agriculture, Singaperbangsa University, Karawang, located in Karawang Regency and start from April 2023 – May 2023. The research method used was a Completely Randomized Factorial Design. There are 2 factors consisting of 21 treatments. The first factor was the pH of PDA media which consisted of 3 levels, namely p1 (pH 6), p2 (pH 7) and p3 (pH8). Second factor was straw mushroom isolate which consisted of 7 levels, namely i1 (Parent P), i2 (Parent S), i3 (FP001), i4 (FP003), i5 (FP017), i6 (FP023) and i7 (FP024). Each treatment was repeated 3 times, resulting in 63 experimental units. The effect of the treatment was analyzed by analysis of variance at the 5% level and if it was significant to find out the best treatment it was continued with a DMRT at the 5% level. The results showed that there was an interaction effect between several F3 isolates of straw mushroom (Volvariella volvaceae) Faperta Unsika and different pH of PDA media on the diameter of mycelia colonies, mycelia growth rate and growth rate of mycelia. Treatment of PDA media with pH 8 and straw mushroom (Volvariella volvaceae) isolate Faperta Unsika FP003 gave the highest mycelial growth results with a mycelia colony diameter of 7 cm, a mycelia growth rate of 3.08 cm/day and growth rate of mycelia 2.58 cm/day.Keywords: Isolate Faperta Unsika, Mycelia, pH of PDA Media, Straw Mushroom